THE EFFECT OF TURMERIC POWDER ADDITION TOWARD GROWTH AND SURVIVAL RATE OF Cyprinus carpio - Simbolon, Mastiur Afridayanti; Windarti, Windarti; Sarumaha, Herman (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2022)
Turmeric (Curcuma longa Linn.) is one of the natural sources that can be used to improve the appetizer of fish and this improve the growth of that fish. Research aimed to understand the growth and survival of C.carpio fed with turmeric-enriched pellets was conducted from March to May 2022. There were 4 different dosages of turmeric powder applied, namely T0 (Control), T1 (0.5 g/kg), T2 (1 g/kg), and T3 (1,5 g/kg). The fish was reared in a 25 L container completed with an aerator and filter. The density of fish was 15 fish/container, around 3 g BW and 6 cm TL. The fish was fed ad-satiation, 3 times/day and was reared for 49 days. Sampling was conducted once a week. Results showed that the survival rate of fish in all treatments was good, more than 95 %. The best growth was obtained in T3, as the fish achieved 6.29 g BW and 7.61 cm TL. While the fish of other treatments were lower, they were T0 (4.60 g; 6.72 cm), T1 (4.73 g; 6.85 cm), and T2 (4.99 g; 7.03 cm). The best FCR was also found in T3 (1.37) and the FCR of other treatments were T0 (2.28), T1 (2.10) and T2 (1.97) respectively. Data obtained indicate that the addition of turmeric powder improves the growth as well as the FCR of C.carpio.